5-n-alkylresorcinol-based metabolic response of rice to the interaction with Burkholderia glumae: a chemical characterization of the temporal and spatial variations depending on environmental conditions. Issue 1 (31st December 2022) - Marentes-Culma, Ronald; Cuellar-Cuestas, Carolina; Ardila, Harold Dubán; Coy-Barrera, Ericsson
ABSTRACT: Burkholderia glumae is a relevant worldwide pathogen of rice. B. glumae unfavorably affects the throughput of rice crops provoking seedling death and blight panicles. Different intrinsic and extrinsic factors influence the interaction, the host physiological response and its metabolic performance, e.g. biosynthesis of protecting metabolites such as 5- n -alkylresorcinols (AR). However, the metabolic responses of rice interacting with B. glumae and involving different factors are still unraveled. Thus, AR variations in two Colombian rice genotypes, grown in two climatically different locations and inoculated independently with two B. glumae strains were evaluated through total AR content and LC-MS-based characterization. AR accumulated in rice plants at different levels depending on genotypes, plant parts and phenological stages. Rice genotypes were affected by pathogen inoculation, promoting AR variations. Such pathogen-mediated influence was also affected by the test factors. This AR-based rice response against B. glumae constitutes a contribution to understand better this biotic interaction.